Three-Month Outcomes of SMILE Pro with the VISUMAX 800 for Myopic Astigmatism in a Large Population - Cung HS; Tran LHT; Tran TN (Clinical Ophthalmology)
Hong Son Cung,1,2 Lan Huong Thi Tran,1,2 Thanh Ngoc Tran1,2 1Vietnam National Eye Hospital, Ha Noi, Vietnam; 2Hong Son Eye Hospital, Ha Noi, VietnamCorrespondence: Lan Huong Thi Tran, Vietnam National Eye Hospital, Ha Noi, Vietnam, Email huonglanmat1991@gmail.comPurpose: To report the visual and refractive outcomes of small-incision lenticule extraction (SMILE) Pro using a 2 MHz femtosecond laser for myopic astigmatism in a large population of Vietnamese patients.Methods: This was a retrospective clinical study of subjects that underwent keratorefractive lenticule extraction (KLEx) with the VISUMAX 800 at Hong Son Eye Hospital (Ha Noi, Vietnam) between June 2023 and October 2023. Primary outcome measures of monocular uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), and refraction, including vector analysis, were evaluated at 3-months postoperatively. Secondary outcome measures of intraoperative and postoperative complications were also recorded.Results: A total of 765 eyes from 389 patients (60.66% women, mean age of 23.54± 5.20 years) were analyzed 3 months after surgery. The mean preoperative spherical equivalent refraction was − 5.98± 2.26 D. The postoperative spherical equivalent refraction was within ± 0.50 D of the intended target in 81% and within ± 1.00 D in 97% of eyes. The mean spherical equivalent refraction was − 0.11± 0.45 D. UDVA was 20/25 or better in 92% and 20/32 or better in 97% of eyes. The mean postoperative UDVA and CDVA values were 0.05± 0.09 and 0.00± 0.02 logMAR, respectively. There was no change in CDVA in 99% of eyes. Efficacy index was 0.92, and safety index was 1.00. One eye (0.13%) had a suction loss, which resulted in a lenticule remnant. No other complications were reported during surgery or the postoperative follow-up period.Conclusion: The current study, carried out on a large cohort of Asian patients, showed SMILE Pro with the VISUMAX 800 was safe and effective for treating myopic astigmatism.Keywords: SMILE, femtosecond laser, myopia, astigmatism